The second species of Triartiger Kubota (Coleoptera: Staphylinidae: Pselaphinae) from China’s mainland - Yin, Zi-Wei; Du, Jing-Zhe (Zootaxa, 2024)
Triartiger jiangxinongda Yin & Du, sp. nov. (Clavigeritae: Clavigerini) is described from Meiling National Forest Park, Jiangxi, East China based on two male adults collected by a flight intercept trap, which represents the second known species of the genus from China’s mainland. The species is morphologically most similar to the recently documented T. spatulatus Yin distributed in Fujian, and differs by the relatively shorter head, differently patterned setation of the vestiture, and a more slender aedeagus.